Status of Giant Squirrel (Ratufa indica) in Similipal Tiger Reserve, Orissa, India - Rout, S. D.; Swain, D. (Indian Forester, 2005)
The Similipal Tiger Reserve (21Â°28’ - 22Â°08’ N latitude, 86Â°04’ - 86Â°37’ E longitude) of Mayurbhanj District, Orissa is one of the nine initially constituted Tiger Projects in India. The Reserve is a virgin sub-tropical forest and is a repository of large flora and fauna, which are a mixture of South Indian, North Indian and Andaman species. The Malabar or Indian Giant squirrel (Ratufa indica) which is distributed in Peninsular India, was also recorded in Similipal forest. According to the last census there were 10,660 squirrels estimated in Similipal Tiger Reserve. During the study period a total of 24 species of food plants have been recorded. Giant squirrel depends majority of time on seeds of some tree species. The study reveals that the squirrels were preferred more the petiole of leaf followed by fruit and bark of the tree as their food in all the months of the year. Data on nesting habits were recorded and a squirrel used more than 4 nests within a territory either to escape from nest predator or may provide shelter from natural calamities. The present communication deals with the study on the status of Giant squirrel (Ratufa indica) in Similipal Tiger Reserve, Orissa, India.